The Malaysian Contracts Act 1950: Some Legislative and Judicial Developments Towards a Modern Law of Contract - Cheong, May Fong (Journal of Malaysian and Comparative Law, 2009)
The Malaysian Contracts Act 1950, modelled on the Indian Contract Act 1872, has encapsulated contract law tenets of English nineteenth-century laissez faire market capitalism, freedom of contract and classical contract law. Through time, however, new forces have challenged the traditional views of contract law, supported by legislative reforms and judicial developments. The shift from classical to modern contract law has been taken cognisance of and is generally accepted in the common law world. This essay, however, aims to show this movement in Malaysian contract law as provided in the Contracts Act 1950 and as interpreted by the Malaysian courts. It evaluates whether and to what extent values of modern contract law, such as fairness and justice, have influenced the law, and analyses the main theme of vitiation of free consent in the Contracts Act 1950 through the doctrines of unconscionability, undue influence and coercion. Reference will also be made to the law in the United Kingdom and other Commonwealth countries. The essay concludes by exploring the roles of legislative reform and judicial interpretation in developing Malaysian contract law, as embodied within classical law concepts in the Contracts Act 1950, towards a modern law of contract.